Les porcs dans la documentation textuelle paléo-babylonienne - Lion, B. (Journal for semitics, 2007)
Although there are very few studies dedicated to pigs in the Ancient Near East, the documentation in cuneiform texts dealing with this animal happens to be rich and of great variety. During the Old Babylonian period, its presence is attested in the whole of Mesopotamia, in the south (Larsa), as in the north (Sippar, Kish, Manan?) of Babylonia, also in Upper Mesopotamia (Chagar Bazar, Tell Rimah). The animal occurs in private archives as well as in administrative documents, and even law collections (among which the Laws of Hammurabi) deal with stealing pigs which belong to the temple, to the palace or to private persons. The texts list pigs in inventories, touch on grain fattening procedures, give their price, specify for which festivals they were delivered or quote the number of piglets given as food rations. Some lawsuits recalling the Hammurabi code deal with pig robberies. The animals were slaughtered and eaten, and the lard was also used.